METODE PENGEMBANGAN MORAL DAN DISIPLIN BAGI ANAK USIA DINI (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2018)
Early childhood development is classified in rapid development, including physical, cognitive, emotional, social, and moral development. Moral is the derivation of the Latin word plural of